Seasonal dynamics in microbial trace metals transporters during phytoplankton blooms in the Southern Ocean - Yanhui Kong; Rui Zhang; Stéphane Blain; Ingrid Obernosterer (Environmental Microbiology, 2024)
Trace metals are required as cofactors in metalloproteins that are essential in microbial metabolism and growth. The microbial requirements of diverse metals and the capabilities of prokaryotic taxa to acquire these metals remain poorly understood. We present here results from metagenomic observations over an entire productive season in the region off Kerguelen Island (Indian Sector of the Southern Ocean). We observed seasonal patterns in the abundance of prokaryotic transporters of seven trace elements (zinc [Zn], manganese [Mn], nickel [Ni], molybdenum [Mo], tungsten [W], copper [Cu] and cobalt [Co]) and the consecutive spring and summer phytoplankton blooms were strong drivers of these temporal trends. Taxonomic affiliation of the functional genes revealed that Rhodobacteraceae had a broad repertoire of trace metal transporters (Mn, Zn, Ni, W and Mo) and a more restricted set was observed for other prokaryotic groups, such as Flavobacteriaceae (Zn), Nitrincolaceae (Ni and W) and Thioglobaceae (Mo). The prevalence of trace metal transporters within a prokaryotic group, as determined on the family level, was overall confirmed in representative metagenome‐assembled genomes. We discuss the potential involvement of prokaryotic groups in processes related to organic matter utilisation that require these metals and the consequences on carbon and trace metal cycling in surface waters of the Southern Ocean.